La potencia y la resistencia aeróbica en jóvenes atletas - Villa Betún, Erika Andreina (2025)
This research, entitled “Power and Aerobic Endurance in Young Athletes,” aims to analyze the influence of a power exercise training program on the improvement of aerobic endurance in young athletes from the Bolívar Sports Federation. The study is based on the premise that these fundamental physical abilities—power and endurance—are essential in various sports disciplines and must be trained according to the physiological characteristics of youth athletes. A pre-experimental design with a quantitative approach was applied, conducting pre- and post-tests using the Course Navette test with a sample of 10 athletes, both male and female, aged between 15 and 18 years. Over 12 weeks, participants completed a structured power exercise program with progressive difficulty and controlled intensity. The post-test results showed significant improvements in aerobic endurance, with an increase in the average test duration and a shift in athlete performance to the “excellent” level. Statistical analysis using the Student's t-test showed a significant difference between pre- and post-test data (p < 0.001), confirming the program's effectiveness. This study contributes to the methodological planning of sports training in youth stages, offering a practical alternative to simultaneously enhance power and aerobic endurance. It concludes that power development can positively impact aerobic performance, making it an effective strategy for coaches aiming to optimize young athletes’ physical performance